Incidental Pancreatic Lipomas: A Case Series on 64 Slice MDCT done for Different Pathologies (Nepalese Journal of Radiology, 2012)
Pancreatic lipomas are rare benign lesions, with only 50 cases being documented in the current literature to the best of our knowledge. We describe four cases of intrapancreatic lipomas from a single institution, all incidentally found using multi detector computed tomography within a 6-month period. Computed tomography depicted lipomas as homogeneous, nonenhancing, well-marginated lesions with a density coefficient consistent with adipose tissue. DOI: http://dx.doi.org/10.3126/njr.v1i1.6318 Nepalese Journal of Radiology Vol.1(1): 23-26